DEVELOPING STUDENTS' RATIONAL THINKING THROUGH INTERACTIVE EDUCATIONAL METHODS: RESULTS OF EXPERIMENTAL RESEARCH (American Journal of Pedagogical and Educational Research, 2025)
This experimental study examines the effectiveness of interactive teaching methods in developing students' rational thinking. The paper presents the results of a pedagogical experiment conducted with 120 students during the 2023-2024 academic year. Modern interactive methods were used: case studies, business games, project work, discussions, and digital educational technologies. The results showed a significant improvement in rational thinking in the experimental group: critical thinking improved by 42%, analytical skills by 38%, and logical thinking by 45%. The study confirmed the hypothesis that the systematic use of interactive methods contributes to the development of sustainable rational thinking skills.